2021
DOI: 10.3390/w13121652
|View full text |Cite
|
Sign up to set email alerts
|

Not All Rivers Are Created Equal: The Importance of Spring-Fed Rivers under a Changing Climate

Abstract: In the Western United States, volcanic spring-fed rivers are anticipated to become increasingly more important for salmonids and other native fishes, as these rivers will retain coldwater habitats as the climate warms. Despite this, little is known about the hydro-biogeochemical interactions within these ecosystems. A review of existing literature on spring-fed rivers, coupled with a decade of research on volcanic spring-fed rivers of northern California, finds that these systems are exceptionally productive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 149 publications
1
15
0
Order By: Relevance
“…However, studies are limited compared to those examining the role of the Earth’s surface factors. In freshwater, the watershed geology controls the thermal heterogeneity by providing inputs of cold groundwater (e.g., Tague et al 2007, McDonnell et al 2015, Lusardi et al 2021). In the context of Antarctic active layers, Hrbáček et al (2017) reported a distinct ground thermal regime between lithologically different sites due to thermal conductivity controlled by the geology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies are limited compared to those examining the role of the Earth’s surface factors. In freshwater, the watershed geology controls the thermal heterogeneity by providing inputs of cold groundwater (e.g., Tague et al 2007, McDonnell et al 2015, Lusardi et al 2021). In the context of Antarctic active layers, Hrbáček et al (2017) reported a distinct ground thermal regime between lithologically different sites due to thermal conductivity controlled by the geology.…”
Section: Introductionmentioning
confidence: 99%
“…Watershed geology affecting water permeability in the subsurface layers contributes to groundwater inputs (Mushiake et al 1981, Boulton and Hancock 2006, Cornu et al 2013). Thermal heterogeneity controlled by geology in running water ecosystems has been increasingly highlighted (Tague et al 2007, McDonnell et al 2015, Lusardi et al 2021). In addition to the cooling process at the streambed/water interface, namely the groundwater contribution, climatic conditions, such as air temperature and precipitation, determine the water temperature (Caissie 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we reviewed existing studies on water quality conditions at each study site to determine whether groundwater contributions may affect water temperature or water quality conditions such that increased or decreased baseflow may be needed during the dry season. While groundwater-influenced streams provide reliable water supply during the dry season, they are particularly notable for providing high water quality with limited contaminants from their adjacent wetlands and deep aquifer sources (Lusardi et al, 2021). Groundwater-derived baseflows also typically provide relatively cool water during the dry season and warm water during the wet season, helping to mitigate physiologically stressful seasonal extremes in temperature (Davidson et al, 2010).…”
Section: California Environmental Flows Frameworkmentioning
confidence: 99%
“…Groundwater-influenced streams have also been shown to provide highly productive rearing habitat for salmon and other native fishes in California because of their naturally higher levels of nutrients, including nitrate and phosphate (Lusardi et al, 2016;Lusardi et al, 2020). The combination of optimal thermal regimes, high productivity, and stable hydrologic conditions make groundwater-influenced streams critical refugia for coldwater species in arid and semi-arid environments such as California (Lusardi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to identify climate refugia are tackling increasing ecological complexity by considering a broader suite of environmental variables (Lusardi et al., 2021) and organismal traits (Ebersole et al., 2020; Morelli et al., 2020; Troia et al., 2019), yet they often overlook the role of seasonal foraging habitat in the persistence of thermally sensitive animals in landscapes with environmental extremes. Productive downstream habitats that support seasonal foraging, such as lakes (our study), floodplains (Katz et al., 2017), and estuaries (Hayes et al., 2011), are typically more degraded and less protected than headwater streams due to historical patterns of human development.…”
Section: Discussionmentioning
confidence: 99%